Development of a Duplex PCR-NALFIA Assay for the Simultaneous Detection of Macrophomina phaseolina and Verticillium dahliae Causal Agents of Crown and Root Rot of Strawberry - Viola Papini; Angelo Meloni; Susanna Pecchia (Agriculture)
Strawberry crown and root rot diseases are caused by soil-borne pathogens including Macrophomina phaseolina (Mp) and Verticillium dahliae (Vd). The symptoms caused by these pathogens are very similar and difficult to distinguish, and traditional culture-based detection methods are laborious, time-consuming, and slow in providing results. In this work, we developed a duplex PCR-NALFIA assay using two pairs of species-specific primers labeled at the 5′ end with different molecules for the simultaneous identification of Mp and Vd. For the NALFIA assay, a lateral flow device (LFD) for the detection of two analytes was used. The method was developed by single and duplex PCR (Mp, Vd, Mp + Vd) using increasingly complex biological systems: (i) DNA from pure cultures of the pathogens; (ii) DNA from artificially inoculated cut melon stems; and (iii) DNA from artificially inoculated strawberry plants cv. Aromas. The duplex PCR protocol was effective in detecting the two pathogens within melon tissues and provided good results with strawberry crown tissues only when the DNA samples were purified by removing the PCR inhibitors. The amplicons were used for both agarose gel electrophoresis (AGE) and NALFIA assays and demonstrated the greater sensitivity of the NALFIA assay (10 pg) for simultaneous detection of the two pathogens.